Land Consolidation as One of The Solutions in Providing Green Open Space in Urban Areas in Indonesia - Hutapea, Maria; Krismantoro, Damianus; Fransiska, Eudia Viona (West Science Law and Human Rights, 2025)
The increasing price of land in urban areas makes it difficult for the government to provide land for the development of Green Open Space. Land Consolidation is a land policy regarding the reorganization of land tenure and use as well as to improve environmental quality and maintenance of natural resources by involving active community participation. In this case, the government does not need to provide compensation that requires very large funds because the principle used in Land Consolidation is to build without displacement. Land Donation for Development which will be used for public and social facilities and green open spaces. This research aims to find out how the implementation of Land Consolidation in Indonesia as one of the solutions in the provision of land to provide land for the purposes of green open space development and the obstacles faced and their resolution. The research method used is normative juridical method. The data source used is secondary data. The method of data collection is done by means of literature study. Data processing is done by descriptive analytical method. Based on the existing fact that the implementation of Land Consolidation in Indonesia, especially to provide for the development of Green Open Space in urban areas, is often constrained, given the high price of land in urban areas. Therefore, the existence of Land Consolidation can be used as one of the ways to obtain land for the development of Green Open Space in urban areas in Indonesia.